Geronticide : killing the elderly - Brogden, Michael (Jessica Kingsley Publishers, 2001)
Annotation The increasing elderly population poses many economic and ethical questions for modern society. One of the most topical and controversial of these is the debate about euthanasia. Drawing on a variety of historical, contemporary, anthropological and literary sources, this book considers the present-day debates about the sanctity of elderly lives and the question of euthanasia. Geronticide: Killing the Elderly seeks to place the current debate in a wider historical and social context, while providing a comprehensive overview of current academic and professional concerns. This thorough, authoritative book will be a useful, thought-provoking read for anyone involved in working with the elderly.